Implementation of demonstration methods in improving understanding of the Qur'an and Hadith in junior high schools - Kholidah Nur (TA`DIBUNA, 2025)
The purpose of this study is to examine how the demonstrative approach is used in Madrasah Tsanawiyah to enhance students' comprehension of the Al-Qur'an Hadith content. The demonstration method is used to connect theory with practice, so that students not only memorize the texts of the Al-Qur'an and Hadith, but can also apply them in everyday life. The classroom action research (CAR) method used in this study was carried out in two cycles, each of which included planning, execution, observation, and reflection. Tests, interviews, and observation were used to gather data both before and after the demonstration approach was put into practice. The results showed a significant increase in students' understanding of the Al-Qur'an Hadith material, with 91.06% of students achieving learning mastery in the second cycle. The demonstration method has been proven effective in increasing student participation, learning motivation, and their social skills. However, this study is limited to one location and a small sample, so it is recommended to conduct further research with a more comprehensive design and a larger sample. This study contributes to the development of Islamic religious learning methods that are more applicable and interesting for students.